Enzyme-linked immunosorbent assay for serological diagnosis of Nocardia brasiliensis and clinical correlation with mycetoma infections. - Salinas-Carmona, M C (1993)
We previously identified three immunodominant antigens obtained from a Nocardia brasiliensis cell extract and recognized by sera from mycetoma patients (M. C. Salinas-Carmona, L. Vera, O. Welsh, and M. Rodríguez, Zentralbl. Bakteriol. 276:390-397, 1992). In the present work, we obtained a crude extract from a mass culture of N. brasiliensis HUJEG-1 and purified two immunodominant antigens, the 26- and 24-kDa proteins, by using simple physiochemical techniques. With these antigens, we developed a conventional solid-phase enzyme-linked immunosorbent assay and tested 30 serum samples from mycetoma patients, 29 from tuberculosis patients, 24 from a leprosy group, and 31 from healthy individuals. Our results show for the first time statistically significant differences in serology among these groups. All mycetoma patients with a positive culture for N. brasiliensis had absorbance values higher than 0.3. On the other hand, the mycobacterium-infected patients as well as the healthy individuals all had absorbance values below that level. Moreover, we found a close correlation between the clinical condition of the mycetoma patients and the anti-26- and anti-24-kDa protein antibody concentrations. We therefore propose the use of this assay in routine clinical laboratories to confirm the diagnosis of N. brasiliensis infection in human mycetoma cases. In addition, the possible application of this assay in the serodiagnosis of Nocardia asteroides infection is also discussed.